Urgensi Kekerasan di Satuan Pendidikan: Bagaimana Peran Permendikbudristek PPKSP? - Wahyuni, Dela Sri; Asbari, Masduki; Desrifitri, Arum Dalu (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to determine the prevention and control of violence in educational units. Based on or Permendikbukristek PPKSP, this study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's Smart Character Youtube channel entitled